Regarding "Percentile-Based Journal Impact Factors" (Spring 2009) - A. Ben Wagner (Issues in Science and Technology Librarianship)
A letter to the editor is presented in response to the article "Percentile-Based Journal Impact Factors: A Neglected Collection Development Metric."